Montelukast protects against ischemia reperfusion induced funtional, histological and biochemical changes in rat urinary bladder - (:unkn) unknown (My University, 2006)
[No abstract available]
Keywords: Bladder; Ischemia; Montelukast; Oxidative injury; Reperfusion